Anti-TIF1γ antibodies (anti-p155) in adult patients with dermatomyositis: comparison of different diagnostic assays. Issue 6 (30th January 2012) - Labrador-Horrillo, Moises; Martínez, Maria Angeles; Selva-O'Callaghan, Albert; Trallero-Araguás, Ernesto; Balada, Eva; Vilardell-Tarrés, Miquel; Juarez, Candido
Abstract : Background: A new myositis-specific autoantibody (anti-p155) directed against transcriptional intermediary factor 1 γ (TIF1γ) has been described as a good marker of cancer-associated myositis (CAM). Objective: To analyse the feasibility of detecting this autoantibody in patient serum samples using new assays with commercially available recombinant TIF1γ. Methods: The study included 90 Spanish patients with dermatomyositis (DM), classified as clinically amyopathic DM, CAM, or DM without cancer. Anti-TIF1γ antibodies were detected by ELISA and immunoblot techniques and compared with anti-p155 antibody detection by protein immunoprecipitation assays with radiolabelled HeLa cells. The κ coefficient was used to compare the agreement between the different tests. Results: Serum samples from 23 (25.6%) and 20 (22.2%) patients with DM recognised TIF1γ by ELISA and immunoblot, respectively. ELISA (κ=0.91) and immunoblot (κ=0.88) showed excellent agreement with immunoprecipitation analysis (anti-p155). Good concordance (κ=0.91) was also seen between ELISA and immunoblot. Conclusions: Excellent agreement was found between anti-p155 detected by immunoprecipitation and anti-TIF1γ detected by ELISA or immunoblot. These data indicate that identification of this autoantibody can be reliably performed in a standard laboratory setting, with potential application in clinical practice for cancer screening in adult patients with DM.